'I should have taken that further' – missed opportunities during cardiovascular risk assessment in patients with psoriasis in UK primary care settings: a mixed‐methods study. (4th September 2015) - Nelson, Pauline A.; Kane, Karen; Chisholm, Anna; Pearce, Christina J.; Keyworth, Christopher; Rutter, Martin K.; Chew‐Graham, Carolyn A.; Griffiths, Christopher E.M.; Cordingley, Lis; ,
Abstract: Background: Unhealthy lifestyle is common in psoriasis, contributing to worsening disease and increased cardiovascular disease (CVD) risk. CVD risk communication should improve patients' understanding of risk and risk‐reducing behaviours; however, the effectiveness of risk screening is debated and evaluation currently limited. Objective: To examine the process of assessing for and communicating about CVD risk in the context of psoriasis. Design: Mixed‐methods study in English general practices to (i) determine proportions of CVD risk factors among patients with psoriasis at risk assessment and (ii) examine patient and practitioner experiences of risk communication to identify salient 'process' issues. Audio recordings of consultations informed in‐depth interviews with patients and practitioners using tape‐assisted recall, analysed with framework analysis. Participants: Patients with psoriasis ( n = 287) undergoing CVD risk assessment; 29 patients and 12 practitioners interviewed. Results: A high proportion of patients had risk factor levels apparent at risk assessment above NICE recommendations: very high waist circumference (52%), obesity (35%), raised blood pressure (29%), smoking (18%) and excess alcohol consumption (18%). There was little evidence of personalized discussion about CVD risk and behaviour change support in consultations. Professionals reported a lack of training in behaviour change, while patients wanted to discuss CVD risk/risk reduction and believed practitioners to be influential in supporting lifestyle management. Conclusions: Despite high levels of risk factors identified, opportunities may be missed in consultations to support patients with psoriasis to understand CVD risk/risk reduction. Practitioners need training in behaviour change techniques to capitalize on 'teachable moments' and increase the effectiveness of risk screening.